Rapid Progression of Angioimmunoblastic T Cell Lymphoma Following BNT162b2 mRNA Vaccine Booster Shot: A Case Report - Goldman, Serge; Bron, Dominique; Tousseyn, Thomas; Vierasu, Irina; Dewispelaere, Laurent; Heimann, Pierre; Cogan, Elie; Goldman, Michel (Frontiers in Medicine, 2021)
Since nucleoside-modified mRNA vaccines strongly activate T follicular helper cells, it is important to explore the possible impact of approved SARS-CoV-2 mRNA vaccines on neoplasms affecting this cell type. Herein, we report and discuss unexpected rapid progression of lymphomatous lesions after administration of a BNT162b2 mRNA vaccine booster in a man recently diagnosed with AITL.